Digital Ethnobiology: exploring the digisphere in search of traditional and indigenous knowledge and practices - De Meyer, Emiel; Ceuterick, Melissa (Ethnobotany Research and Applications, 2022)
During the last decades, under influence of globalization, the scope of ethnobiological research has expanded. Rapidly developing technology, telecommunication, the internet, and social media promote the occurrence and maintenance of ties within and between communities through multifaceted ways of digital communication. This often gives rise to digital or virtual communities in which knowledge, perspectives and ideas are shared. We want to highlight the significance of these virtual digital social ties and the associated exchange of ethnobiological knowledge among and between ethnic groups, which can lead or has led to an extension of the ethnobiological field of study to a digital or virtual environment. We propose the new term "digital ethnobiology" as "the scientific study of dynamic relationships between peoples, biota, and environments in a virtual or digital environment". We support our term with four case studies from the field of urban ethnobotany, sociology, and agribusiness development. We discuss opportunities, concerns, challenges, future perspectives, and raise some relevant questions on good research practices. Keywords: digital ethnobiology; digital networks; migrant groups; urban ethnobotany